2017
DOI: 10.1136/archdischild-2016-311787
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-minute consultation: The healthy child: “My child is a fussy eater!”

Abstract: Feeding a child is an emotive experience. Selective eating (often referred to as fussy eating) is a typical part of early childhood but can cause significant anxiety to parents. This article covers the factors that influence the development of selective eating, the key points to elicit in history and examination, and evidence-based advice for parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Caregivers should be reassured that picky eating is a common stage of development that is unlikely to cause any permanent harm to the child's long-term development. Levene and Williams (67) have set out detailed strategies for parents/caregivers and include information on sample portion sizes for preschool children, a sample plan for graded exposure to food items, and a list of resources for parents and health professionals. Key strategies described in greater detail include: (1) having realistic expectations of children's portion sizes; (2) graded and repeated exposure to unfamiliar foods (10-15 positive experiences may be needed); (3) using non-food rewards to provide motivation; (4) having a positive approach, avoiding negativity and pressure to eat; (5) parental modelling of eating fruit and vegetables and trying unfamiliar foods; (6) promoting appetite by limiting snacks and energy-providing drinks such as milk, juice and soft drinks in between meals; (7) having social food experiences such as family meals with all members eating the same food; (8) focusing on long-term goals and being consistent.…”
Section: Advice For Health Professionals and Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers should be reassured that picky eating is a common stage of development that is unlikely to cause any permanent harm to the child's long-term development. Levene and Williams (67) have set out detailed strategies for parents/caregivers and include information on sample portion sizes for preschool children, a sample plan for graded exposure to food items, and a list of resources for parents and health professionals. Key strategies described in greater detail include: (1) having realistic expectations of children's portion sizes; (2) graded and repeated exposure to unfamiliar foods (10-15 positive experiences may be needed); (3) using non-food rewards to provide motivation; (4) having a positive approach, avoiding negativity and pressure to eat; (5) parental modelling of eating fruit and vegetables and trying unfamiliar foods; (6) promoting appetite by limiting snacks and energy-providing drinks such as milk, juice and soft drinks in between meals; (7) having social food experiences such as family meals with all members eating the same food; (8) focusing on long-term goals and being consistent.…”
Section: Advice For Health Professionals and Caregiversmentioning
confidence: 99%
“…Many children go through a period of time as a picky eater and it can be difficult for health providers to judge when intervention is needed. It has been suggested that this decision should be based on whether the child's feeding behaviour is problematic for health, development, education, psychological wellbeing and socialisation ( 67 ) . Referral to a paediatric dietitian or psychologist is recommended for children who fulfil the diagnostic criteria for Avoidant/Restrictive Food Intake Disorder or who have special dietary requirements for a chronic disease such as type 1 diabetes, a metabolic disorder or cystic fibrosis, or who have learning difficulties or autistic spectrum disorders.…”
Section: Advice For Health Professionals and Caregiversmentioning
confidence: 99%
“…To effort to promote healthy food at home, parents especially mothers have several obstacles both from within themselves and from the environment. Constraints experienced include such as busy parents so that there is no time, the cost of preparing healthy food in the house, the high desire of children to consume junk food, and the lack of support from the family due to picky eating too several other family members (Levene & Williams, 2017). Need for motivation as well as a better understanding of mothers about how to encourage meat, seeds, fruits, and vegetables to be included in food intake in children will help promote healthy eating habits (Edelson, Mokdad, & Martin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some of participants at age 13 years who were classified as picky eaters at age 3 years had emerging eating disorders: evidence for an effect of being a picky eater in early childhood on the development of later eating disorders is conflicting, with some authors reporting an association [20] but others not [44]. Strategies for parents to help their children overcome picky eating before it becomes persistent include repeated exposure of food, having realistic expectations of portion sizes, having a positive approach, not providing snacks between meals or letting the child drink excessively and providing social food experiences and consistency [45].…”
Section: Discussionmentioning
confidence: 99%